Multifunctional blazed gratings for multiband spatial filtering, retroreflection, splitting, and demultiplexing based on C 2symmetric photonic crystals - Serebryannikov, Andriy E. (2022)
The concept of multifunctional reflection-mode gratings that are based on rod-type photonic crystals (PhCs) with C 2 symmetry is introduced. The specific modal properties lead to the vanishing dependence of the first-negative-order maximum on the angle of incidence and the nearly sinusoidal redistribution of the incident-wave energy between zero order (specular reflection) and first negative diffraction order (deflection) at frequency variation. These features are key enablers of diverse functionalities and the merging of different functionalities into one structure. The elementary functionalities, of which multifunctional scenarios can be designed, include but are not restricted to multiband spatial filtering, multiband splitting, retroreflection, and demultiplexing. The proposed structures are capable of multifunctional operation in the case of a single polychromatic incident wave or multiple mono-/polychromatic waves incident at different angles. The generalized demultiplexing is possible in the case of several polychromatic waves. The aforementioned deflection properties yield merging demultiplexing with splitting in one functionality. In turn, it may contribute to more complex multifunctional scenarios. Finally, the proposed PhC gratings are studied in transmissive configuration, in which they show some unusual properties.